Development and evaluation of the standard adenotonsillectomy clinical pathway in Hospital Universiti Sains Malaysia - Lawal, Basheer (2016)
Introduction Patient care variation is an important source of concern in health care delivery. It main sources are in the area of availability of health care services, lower use of medical evidence, and the professional uncertainties. To reduce this variation many guidelines and evaluating tools were created from evidence base medicine practice; one of this tool is clinical pathway (CP), a multidisciplinary structure care plan that detailed essential steps in the care of a patient with specific clinical problems, it supports and translates clinical guides to the local protocol. Hospital Universiti Sains (Hospital USM) had implemented clinical pathway in 2012 and currently conducting a survey on the CP implementation involving eleven specialities, adenotonsillectomy was selected under ORL-HNS. Objectives: To evaluate the standard Clinical Pathway of adenotonsillectomy patients in Hospital USM. Methodology: This was a cross-sectional comparative study conducted over a period of eighteen months in Hospital USM from March 2014 to September 2015.The Universiti Research Ethics Committee (Human) approval has been obtained. Information used in this study was retrieved from implemented CP patient information form and from (Hospital USM) Medical Record Unit. Case note of patients who fulfil inclusion criteria were selected in nonrandomized pattern and reviewed individually for both clinical pathway (CP) and non-clinical pathway (non CP) groups over a period of six months. The data obtained was stored in software, compared and analyses. Results: Total of 60 patients were involved in this study 30 in each CP and non CP groups. 18 females, 12 males were involved in CP group and 16 females and 14 males were involved in non CP group. The average age of participant was13.9 years and 17.1 years in CP and non CP groups respectively. The estimated length of stay observed in this study were 0.9833 and 1.05 for non CP and CP group respectively. The result did not show any statistically observed difference between the groups (Z=-.853; p=.393>.05). Two and six post-operative complications were observed in both non CP and CP groups respectively, Z= -1.506, (P value =0.132 >0.05).There was no significant difference in terms of complications rate between non CP and CP groups. An average estimated adenotonsillectomy cost for CP and non CP group were RM3000 and RM3010 respectively this value was lower than RM4725 quoted in MY-DRG casemix system. An overall 88.4% compliance rate to CP guideline was observed in CP group. Patient complied more with 90%, followed by nurses with 89.9% then doctors with 87.5%. There were eight observed CP variances in this study, six out of this have their sources from a health care provider’s and accounts for75%, two variances were from patients and accounts for 25%. Conclusion This study has evaluated the standard clinical pathway of adenotonsillectomy by looking into specific outcomes of certain parameters such as length of hospital stay, variances, post-operation complications, costing process and overall study effectiveness. The baseline participant demographic data were almost equal between two study groups, there was no significant difference in terms of duration of hospital stay, costing and complications between the two groups. Eight variances were observed in this study, two have their sources from the patients and six from health care providers. The overall compliance of pathway has been very good. We were unable to obtain a cost saving because there was no significant cost difference between the two study groups.